Evaluation and rehabilitation of functional ankle instability in wrestlers - Sofokleous, P.; Gioftsidou, A.; Malliou, P.; Barbas, I.; Kollias, C.; Mirzaei, B.; Curby, D. G. (International Journal of Wrestling Science, 2011)
Objectives: The aim of the present study was to evaluate functional deficits after an ankle sprain in collegiate wrestling students and to examine the effectiveness of two different balance rehabilitation programs on balance ability. Methods: Thirty-three collegiate wrestling students with functional ankle instability were randomly divided into three groups. One subject group (n=10) underwent no specific balance training (control group). The remaining two groups followed an intervention balance program for 4 weeks, 3 times per week, 20 min per time using balance boards. One of the two training groups performed the exercise in a swimming pool- the "pool" group (N=13), and the other at the ground- the "land" group (N=13). Balance ability was assessed before and after the 4 week balance training program. Balance assessment included a stability index recorded on a Biodex Stability System. The functional ability evaluations used the "figure of 8" and "triple jump" tests. Results: The results showed that in both training groups balance and functional ability of the injured leg were significantly improved after the training period. In the final measurements no statistical significant differences between the injured and healthy limb were found. Conclusion: The present study indicates that the performance of balance exercises in or out of the water by wrestling athletes with functional ankle instability improves their balance ability.